Influence of Corporate Social Responsibilities on Society with Special Reference to Banking Sector: Understanding the Impact of Corporate Social Responsibility in the Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper is study about the Influence of corporate social responsibilities adopted by banking sector on society. Social responsibility of business refer to what business do and it benefit to society. Corporate Social Responsibility is also known as Corporate Conscience or Responsible Business. These research paper is based on secondary data. Now-a-days, corporate society has showing great importance in the corporate world which includes financial institutions and banking sector.Nowadays, CSR has become very important for every country. After recognizing the importance of CSR, banks implemented social and environmental programs which benefit themselves and society. CSR refers as strategies which Corporations employ to conduct their own business in a way such as ethical, society friendly and beneficial to society in terms of success.